The effect of anger management, interpersonal communication skills and stress management training on university students’ emotional intelligence / Aghdas Safari - Aghdas, Safari (2015)

(untitled)
The main topic of this research is how teaching anger management, stress management and interpersonal communication skills affects emotional intelligence of female first year university students of Roodehen Islamic Azad University in Iran. The study population is all first year female students of Roodehen Islamic Azad University. The study was carried out on 120 students who were selected by multi-stage randomized sampling method and were divided into the four groups (three experimental and one group as control, with 30 students in each group). Before carrying out the experimental intervention (presentation of the independent variables), the four groups were given the pre-test using the Emotional Intelligence questionnaire (EQi). Then, the students in experimental groups attended five 2-hour training sessions of anger management, five 2-hour training sessions of stress management five 2-hour training sessions of interpersonal communication techniques respectively. One week after the intervention, the four groups were post-tested again using the EQi. The data were analyzed using Ancova method (analysis of covariance) t –test and Mann-Whitney U Test. Results of the study indicate that training in anger management, stress management and interpersonal communication skills will lead to increased Emotional Intelligence of female students, compared with the control group.